LEGAL PROTECTION FOR APPEARERS WHEN THE NOTARY'S EXISTENCE IS UNKNOWN (AFWEZEGHEID) - Yusti Merilistia; Istislam; Yenni Eta Widyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research examines the legal protection of clients when the notary's whereabouts are unknown (afwezigheid). describe and analyze the certainty of legal protection for appearers who are harmed by a notary whose whereabouts are unknown afwezigheid and to analyze and formulate forms of legal protection that can guarantee legal certainty for appearers who are harmed by a notary whose whereabouts are unknown afwezigheid.This research is a normative juridical research through literature study using statutory approach (statute approach) and conceptual approach (conceptual approach). The main issues were analyzed using primary legal materials includingProvisions of Article 463 in conjunction with Article 467 of the Civil Code, provisions of Article 15, Article 16, Article 17, Article 62, Article 63 Article 67, Article 69 and Article 70 of Law Number 30 of 2004 concerning the Position of Notary Public juncto Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 15 of 2020 concerning Procedures for Examining the Supervisory Board of Notaries and Notary Code of Ethics. Legal materials were analyzed based on prescriptive analysis and grammatical and systematic interpretation techniques. Based on the research results it is known thatLegal protection for appearers who are harmed by a notary whose whereabouts are unknown afwezigheid based on the analysis of UUJN Amendment) is weak, because basically (“UUJN”) juncto (“UUJN”) Amendment has accommodated arrangements regarding the presence of a notary in the exercise of his office.